Fat embolism syndrome in patients with bilateral femur fractures: a systematic review and case comparison. (18th April 2022) - Kalbas, Yannik; Seaver, Thomas; Kumabe, Yohei; Halvachizadeh, Sascha; Lempert, Maximilian; Pfeifer, Roman; Marcantonio, Andrew; Pape, Hans-Christoph
Abstract: Objectives: Fat embolism and fat embolism syndrome (FES) remain common complications following long bone fractures. Incidence is highest after bilateral femur fractures. We performed a systematic review of FES after bilateral femur fractures and present two cases. Data sources: Systematic literature search of the Cochrane, EMBASE, MEDLINE, Scopus, and, Web of Science Library databases was performed in August 2021. Terms used including plural and alternate spellings: "fat embolism, ""fat embolism syndrome, ""fat embolus, " and "bilateral femur fracture." Articles in German and English were considered. No time frame was applied. Study selection: Original studies, case series and case reports on fat embolism after bilateral femur fracture were included. Insufficient documentation or patients with relevant previous heath conditions were excluded. Data extraction: Abstracts were organized using EndNote X9 by Carivate. Three authors independently screened the abstracts; cross check of the extracted data was performed by the senior author. Data synthesis: Scarcity of articles only allowed for a qualitative synthesis. Data was compared with our cases and situated within the scientific background. Results: Ten articles were included for qualitative synthesis ( n  = 144 patients). The symptoms were inhomogeneous with neurological deficits being most prominent. Degree of displacement was high, when reported. Although the modes and timing of surgery varied, this appeared unrelated with outcome. Conclusions: FES remains a relevant complication after bilateral femur fractures, despite damage control strategies and improved reaming techniques. Fracture displacement and reduction maneuvers might play a more substantial role in the formation than previously accredited. Level of evidence: 4